SELF ACCEPTANCE PADA REMAJA LAKI-LAKI YANG MELAKUKAN PERNIKAHAN DINI DI DESA KOLONGAN KECAMATAN TALAWAAN - Inggrid Lumentah, Patricia; Becher Sengkey, Stevi; Elisa Jelita Kaunang, Sinta (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Early marriage among adolescent males in Indonesia, particularly in rural areas like Kolongan Village, Talawaan District, disrupts identity formation and psychological adjustment, yet studies predominantly focus on females. This research aims to explore the self-acceptance process using the Kubler-Ross model. Employing a qualitative phenomenological approach, data were gathered from two purposively selected adolescent male participants and six supporting informants via in-depth interviews, observations, and documentation. Analysis followed Miles and Huberman's interactive model with triangulation for validity. Findings reveal a dynamic, non-linear progression through denial, anger, bargaining, depression, and acceptance stages, distinguished by males' externalized expressions like responsibility avoidance and aggression. In conclusion, adolescent males demonstrate adaptive capacity to embrace family roles despite initial resistance, informing targeted psychological interventions.